Penerapan Arsitektur Monolitik Pada Aplikasi Jasa Service Online Tekku Berbasis Web - Sidiq, Muhammad Ali Zafar; Anshori, Muhammad Iqbal; Yaqin, Rifki Ainul (JUKI : Jurnal Komputer dan Informatika, 2024)
This article discusses the application of monolithic architecture in Tekku web-based online service application. The research uses the System Development Life Cycle (SDLC) method to analyze, design, implement, test, and maintain the application. The results include key features such as register, login, technician search, booking, payment, and service status. Testing was conducted using the black-box method to test the functionality of the program, with positive results on the login, logout, accept order, and update service status features. The advantages of monolithic architecture include ease of development and good performance, but the disadvantages are difficulty in developing complex features and difficult scalability. A maintenance phase is conducted to receive feedback and errors from users.